Cross-National Analysis of the Influence of Cultural Norms and Government Restrictions on the Relationship Between Religion and Well-Being - Hayward, R. David (Review of religious research, 2014)
This study examines the interaction between cultural religious norms and governmental restrictiveness as country-level moderators of the relationship between individual religiousness and well-being, including both happiness and physical health. Data come from five waves of World Values survey data from 221 separate surveys conducted in 88 countries, with data from 317,109 individuals. Three dimensions of individual religiousness were assessed, along with corresponding country-level norms aggregated from these measures. Three-way cross-level interactions were tested to examine whether the extent of government restriction modified the relationship between national religious norms and the individual-level association between religious factors and well-being outcomes. Results supported the hypothesis that self-reported religion is most strongly related to greater happiness and better self-reported health in societies where it is freely and widely practiced. In contrast, religiousness may be harmful when it is relatively deviant, and restrictions of freedom may serve to further exacerbate this effect. These results suggest that the positive association between religion and well-being is not universal, but depends upon the right to express religion freely and the opportunity to practice with like-minded others.